Extensive Fatty Replacement of the Pancreas (Pancreatic Lipomatosis) in a Dog. (November 2019) - Muresan, C.; Beteg, F.I.; Lelescu, C.A.; Amorim, I.F.; Rema, A.; Taulescu, M.A.
Summary: A 12-year-old neutered female mixed-breed dog was referred for occasional vomiting that had increased progressively in frequency over the past 3 months. Palpation of the abdomen revealed a firm mass of unknown aetiology, located within the cranial to mid abdomen, while abdominal surgical exploration revealed a well-defined abdominal mass of pancreatic origin. The pancreatic mass caused lateral displacement of the duodenum as well as medial displacement of the pylorus, resulting in impairment of pyloric outflow. Further examination revealed a firm, poorly vascularized and coarsely lobulated structure. The histopathological findings were consistent with severe pancreatic lipomatosis and atrophy. Immunohistochemically, the remnant pancreatic cells were positive for cytokeratins AE1/AE3 and glucagon, and negative for insulin. Routine follow-up with the referring veterinarian showed no evidence of postoperative complications, but the dog continued to deteriorate further and died despite medical management. Pancreatic lipomatosis is a rare condition in small animal practice. The aetiology or predisposing factors have not been identified in animals.